Corporate Governance and Performance of Mutual Funds in Ghana - Ansah, A.Y (University of Ghana, 2015)
This study examined the relationship between corporate governance and performance of mutual funds in Ghana during the 2008 to 2013 period. Using panel regression model, the study found no significant relationship between board size, board composition as well as fund size. However, a significant positive relationship has been found between frequency of corporate board meetings and corporate performance, implying that boards that meet more frequently tend to generate higher financial performance. Fund age was also found to be negatively related to fund performance. As fund age progresses, risk- adjusted returns decrease. The study also discovered a significant negative relationship between gender diversity and fund performance. This research is important because it shed new light on the principal-agent issue in the mutual fund industry. Overall, the findings provided empirical support for agency theory, which suggests that corporate boards that meet more frequently have increased capacity to effectively advise, monitor and discipline management, and thereby improving firm performance
Keywords: CORPORATE; GOVERNANCE; PERFORMANCE; MUTUAL FUNDS; GHANA